Manufacturing climate solutions: carbon-reducing technologies and U.S. jobs - Gereffi, Gary; Dubay, Kristen; Lowe, Marcy (Durham, NC, 2008)
"Manufacturing Climate Solutions presents new research linking U.S. jobs with selected low-carbon technologies that can help combat global warming. In the series, we ask, “In a new global economy increasingly affected by the threat of climate change, what are the U.S. job opportunities in technologies that can reduce carbon emissions?” This ongoing series builds upon a five-technology report released in November 2008 with two new chapters made available in February 2009. Technologies analyzed so far include: LED lighting (November 2008): Leading U.S. manufacturers find it crucial to ensure high quality and to protect their innovations--two good reasons to keep the manufacturing close to home. High-performance windows (November 2008): The U.S. industry faces new, more stringent efficiency criteria that may spur manufacturers to retool production lines and further innovate. Auxiliary power units for trucks (November 2008): Integration of auxiliary power units into long-haul truck manufacturing in the near future will likely increase penetration rates dramatically, with a corresponding boost to manufacturing. Concentrating solar power (November 2008): The new market for concentrating solar power plants has potential to create numerous U.S. manufacturing and construction jobs as U.S. companies grow and foreign firms come to the United States. Super Soil Systems (November 2008): This new technology for treating hog wastes could allow the United States to become a global market leader in a sector where, until now, no adequate alternative has been available. Heat Pump Water Heaters (February 2009): New ENERGY STAR criteria for residential water heaters and new models expected in 2009 could increase demand for these energy-saving products, opening greater opportunities for U.S. component manufacturing in the value chain.